Effect new simple media used for activation poor sperms for Holstein bulls born in Iraq - Ibrahim, OroobaMohammed Saeed; AL-Badry, Kreem Iwaid; Esi, Abeer; Yehia, Zahra; Ibrahim, Faris Faisel; Yahya, Khitam J. (International Journal of Psychosocial Rehabilitation, 2020)
Abstract: Objective: Elevate the percentage of motility in these poor motile ejaculates by using different concentrations of SMART media andexplore the best concentration of SMART media which gives best stimulation with or without the extender which used for manufactured frozen bull semen by Artificial Insemination Center – Iraq\Methods:A total of 44 ejaculates were studied during the period of this twoExperiments:Experiment 1 :Each semen samples were split further into 4 equal aliquots and one part no additiveT1-(control)each other’s three parts were diluted with containing different SMART concentrations viz. T2 0.5ml, T3-1ml, T4-1.5ml, and incubation in water bath 37Cº and evaluation individual motility%, dead and abnormality % after 0 , 30, 45 and 60 minute of storage :Experiment 2: Samples of semen diluted with TFEG diluent were split further into 4 equal aliquots and each one was diluted with containing different SMART concentrations viz.no additive T1=TFEG (control) T2=TFEG+2.5%,TFEG+T3-5%,T4=TFEG+10% after dilution artificial program that included the steps was followed dilution,cooling package in straws 0.25 ml and freezing in liquid nitrogen and post –thawing in water bath 37C° during each steps conducted individual motility%, dead and abnormality% .Results:Experiment 1: Studies indicate that show that addition SMART media caused increase significant (p< 0.05) individual motility% and decrease dead and abnormality % for sperms of Holstein bulls born in Iraq during all periods of storage in water bath at 37 C° and the concentration 1ml of SMART was the best.Experiment 2:Addition 10 % from SMARTto semen diluent gives the best concentration which improved sperm properties of bull semen during different steps of freezing semen (after dilution, cooling and post- thawing).Conclusion:Addnew simple media (SMART) caused improve significant (p< 0.05) in sperm properties of Holstein bulls born in Iraq during storage in water bath at 37 C° and sperm properties of bull’s sperms dilution in TFEGand frozen in liquid nitrogen for 48hr period.